Numerical Simulation and Experimental Investigation of the Viscoelastic Heating Mechanism in Ultrasonic Plasticizing of Amorphous Polymers for Micro Injection Molding - Jiang, Bingyan (Polymers (Basel), 2016)
Ultrasonic plasticizing of polymers for micro-injection molding has been proposed and studied for its unique potential in materials and energy-saving. In our previous work, we have demonstrated the characteristics of the interfacial friction heating mechanism in ultrasonic plasticizing of polymer granulates. In this paper, the other important heating mechanism in ultrasonic plasticizing, i.e., viscoelastic heating for amorphous polymer, was studied by both theoretical modeling and experimentation. The influence mechanism of several parameters, such as the initial temperature of the polymer, the ultrasonic frequency, and the ultrasonic amplitude, was investigated. The results from both numerical simulation and experimentation indicate that the heat generation rate of viscoelastic heating can be significantly influenced by the initial temperature of polymer. The glass transition temperature was found to be a significant shifting point in viscoelastic heating. The heat generation rate is relatively low at the beginning and can have a steep increase after reaching glass transition temperature. In comparison with the ultrasonic frequency, the ultrasonic amplitude has much greater influence on the heat generation rate. In light of the quantitative difference in the viscoelastic heating rate, the limitation of the numerical simulation was discussed in the aspect of the assumptions and the applied mathematical models.